Towards a Profitable Pricing Strategy for Rural Women Indigenous Chicken Breeders: A Case of Rural Village in Zimbabwe - Nani, Gwendoline Vusumuzi; Ronney, Casper (Journal of Economics and Behavioral Studies, 2020)
Indigenous chickens contribute towards poverty reduction, income generation and economic empowerment of rural women. In this regard, employment of a profitable pricing strategy in selling the indigenous chickens becomes fundamental. This study sought to find out the pricing strategies used by rural women indigenous chicken breeders in one purposively selected village in Zimbabwe. An interpretivist paradigm, a qualitative approach and a case study design were employed to examine the issue under review. Seventeen rural women indigenous chicken breeders were key informants. Data collected using semi structured questionnaires and face to face interviews was analysed to discern themes. Results revealed that rural women indigenous chicken breeders did not apply any pricing strategies when selling their chickens. Prices were approximated based on mainly the weight of the chickens. The study concluded that rural women indigenous chicken breeders were ignorant of pricing strategies and factors to consider when determining, prices for their chickens. Further to that, ignorance of appropriate pricing strategies exposed rural women indigenous chicken breeders to exploitation and loss of revenue. In light of this, the study recommended that workshops be conducted by personnel with an accounting background, to train rural women indigenous chicken breeders on the factors to consider in determining profitable prices for their indigenous chickens. The contribution of this study lies in the development of a framework of factors which rural women indigenous chicken breeders could use as a reference point when determining prices for their indigenous chickens.